The Relationship between Environmental Sanitation and the Incidence of Stunting in Toddlers - Paundanan, Matius; Akbar, Hairil; Fajrah, Sitti; Rikwan; Magfira, Aliza; Fitriani (Poltekkes Kemenkes Surabaya, 2025)
Stunting remains a significant nutritional issue among children under five in various regions of Indonesia, including Beka Village, Marawola District, Sigi Regency. Stunting is influenced by several indirect factors, including environmental sanitation, clean water, healthy latrines, wastewater management (Household Wastewater Drainage System), waste management, and hygienic practices. This study aims to examine the relationship between environmental sanitation and stunting incidence among toddlers in Beka Village. This analytical research employs a case-control study design. The study variables include clean water sanitation, healthy latrines, household wastewater drainage system, waste management, and stunting. Data were collected through questionnaires and KMS books, utilizing both primary and secondary sources. Univariate and bivariate analyses were performed using the chi-square test. The study population consisted of all 128 toddlers with stunting, with a sample size of 50 toddlers, including 25 cases and 25 controls. The results indicate a significant relationship between clean water availability (p = 0.020), healthy latrines (p = 0.010), household wastewater drainage system (p = 0.020), and waste management (p = 0.046) with stunting incidence. In conclusion, this study finds a significant association between environmental sanitation factors and the occurrence of stunting in toddlers in Beka Village, Marawola District, Sigi Regency.